Proteksi Ekstrak Daun Pacing Terhadap Resistensi Insulin dan Studi Keamanannya terhadap Fungsi Hati dan Ginjal - Nurfazri Istiqomah, Aulia; Lestari, Kharina Septi; Aligita, Widhya; Rahmah, Farizkah; Novianti, Tamia Rizqi; Raveani, Vina Julia (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Insulin resistance is one of the primary causes of diabetes mellitus, leading to reduced tissue sensitivity to insulin and an increased risk of metabolic complications. The Ethanol Extract of Pacing leaves (EEPL) was evaluated for its potential to prevent insulin resistance in a rat model of diabetes induced by a high-fat, high-fructose diet. The rats were administered EEPL at doses of 150, 300, and 450 mg/kg Body Weight (BW) for 42 days. In addition, a 90-day subchronic toxicity study was conducted to assess potential adverse effects on the liver and kidneys. The results demonstrated that a dose of 300 mg/kg BW significantly improved insulin sensitivity. Biochemical parameters, including creatinine, urea, Serum Glutamic Oxaloacetic Transaminase (SGOT), and Serum Glutamic Pyruvic Transaminase (SGPT), remained within normal ranges, indicating preserved liver and kidney function. However, mild histopathological changes were observed in the kidneys, such as glomerular congestion and tubular necrosis, while the hepatic structure remained normal, with no significant hepatocellular damage. In conclusion, EEPL at a dose of 300 mg/kg BW provides an effective protective effect against insulin resistance, with relatively good safety for long-term use. Nevertheless, further studies are required to confirm its safety in humans.